Quantification of Myocardial Dosimetry and Glucose Metabolism Using a 17-Segment Model of the Left Ventricle in Esophageal Cancer Patients Receiving Radiotherapy - Sha, Xue; Gong, Guanzhong; Han, Chunlei; Qiu, Qingtao; Yin, Yong (Frontiers in Oncology, 2020)
Objective Previous studies have shown that increased cardiac uptake of 18F-fluorodeoxyglucose (FDG) on positron emission tomography (PET) may be an indicator of myocardial injury after radiotherapy (RT). The primary objective of this study was to quantify cardiac subvolume dosimetry and 18F-FDG uptake on oncologic PET using a 17-segment model of the left ventricle (LV) and to identify dose limits related to changes in cardiac 18F-FDG uptake after RT. Methods Twenty-four esophageal cancer (EC) patients who underwent consecutive oncologic 18F-FDG PET/CT scans at baseline and post-RT were enrolled in this study. The radiation dose and the 18F-FDG uptake were quantitatively analyzed based on a 17-segment model. The 18F-FDG uptake and doses to the basal, middle and apical regions, and the changes in the 18F-FDG uptake for different dose ranges were analyzed. Results A heterogeneous dose distribution was observed, and the basal region received a higher median mean dose (18.36 Gy) than the middle and apical regions (5.30 and 2.21 Gy, respectively). Segments 1, 2, 3, and 4 received the highest doses, all of which were greater than 10 Gy. Three patterns were observed for the myocardial 18F-FDG uptake in relation to the radiation dose before and after RT: an increase (5 patients), a decrease (13 patients), and no change (6 patients). In a pairing analysis, the 18F-FDG uptake after RT decreased by 28.93 and 12.12% in the low-dose segments (0–10 Gy and 10–20 Gy, respectively) and increased by 7.24% in the high-dose segments (20–30 Gy). Conclusion The RT dose varies substantially within LV segments in patients receiving thoracic EC RT. Increased 18F-FDG uptake in the myocardium after RT was observed for doses above 20 Gy.